Cell sheet technology-driven re-epithelialization and neovascularization of skin wounds - Cerqueira, M. T. (2014)
Skin regeneration remains a challenge, requiring a well-orchestrated interplay of cell–cell and cell–matrix signalling. Cell sheet (CS) engineering, which has the major advantage of allowing the retrieval of the intact cell layers along with their naturally organized extracellular matrix (ECM), has been poorly explored for the purpose of creating skin substitutes and skin regeneration. This work proposes the use of CS technology to engineer cellular constructs based on human keratinocytes (hKC), key players in wound re-epithelialization, dermal fibroblasts (hDFb), responsible for ECM remodelling, and dermal microvascular endothelial cells (hDMEC), part of the dermal vascular network and modulators of angiogenesis. Homotypic and heterotypic three-dimensional (3-D) CS-based constructs were developed simultaneously to target wound re-vascularization and re-epithelialization. After implantation of the constructs in murine full-thickness wounds, human cells were engrafted into the host wound bed and were present in the neotissue formed up to 14 days post-implantation. Different outcomes were obtained by varying the composition and organization of the 3-D constructs. Both hKC and hDMEC significantly contributed to re-epithelialization by promoting rapid wound closure and early epithelial coverage. Moreover, a significant increase in the density of vessels at day 7 and the incorporation of hDMEC in the neoformed vasculature confirmed its role over neotissue vacularization. As a whole, the obtained results confirmed that the proposed 3-D CS-based constructs provided the necessary cell machinery, when in a specific microenvironment, guiding both re-vascularization and re-epithelialization. Although dependent on the nature of the constructs, the results obtained sustain the hypothesis that different CS-based constructs lead to improved skin healing.